Pathogenicity and immunogenicity of recombinant methyltransferase-defective vesicular stomatitis virus - ZHANG Xiao-dong; SUN Jing; LI Jian-rong; YU Lian (浙江大学学报. 农业与生命科学版, 2011)
To prevent the vesicular stomatitis virus (VSV) disease, using a panel of recombinant VSV (E1764A, S1827A, Y1650A, and F1691A) that were defective in mRNA cap methylation as vaccine to inoculate five-week-old BALB/c female mice through oral route with 1×106 PFU, the pathogenicity and immunogenicity of these viruses were determined. The result showed that recombinant S 1827A, Y1650A, F1691A were attenuated in mice and E1764A was still pathogenic to mice. The immunized mice were challenged with wild type VSV. Mice immunized with S1827A and Y1650A trigged a high level of neutralizing antibody and were protected from virulent challenge. Taken together, the results above demonstrated that methyltransferase (MTase)-defective VSV (S1827A and Y1650A) were not only attenuated in animals, but also exhibited excellent immunogenicity. Therefore, MTase-defective viruses will be good live vaccine candidates against VSV.